2021
DOI: 10.3390/nano11030588
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Radioactive Iodine Using Silver/Iron Oxide Composite Nanoadsorbents

Abstract: Efficient and cost-effective removal of radioactive iodine (radioiodine) from radioactive contaminated water has become a crucial task, following nuclear power plant disasters. Several materials for removing radioiodine have been reported in the literature. However, most of these materials exhibit some limitations, such as high production cost, slow adsorption kinetics, and poor adsorption capacity. Herein, we present silver/iron oxide nanocomposites (Ag/Fe3O4) for the efficient and specific removal of iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Zia et al used a Ag/Fe 3 O 4 nanocomposite which displayed an adsorption capacity of 847 mg/g for I 2 removal from aqueous media. This material exhibited high I – selectivity in the presence of competitive ions (Cl – , Br – , and PO 4 – ), good recyclability, and a removal efficiency of approximately 94% after 7 cycles . Rosenberg et al reported the removal of 131 I from soil by chemical treatment in the presence and absence of I – carrier, H 2 O 2 , and AgNO 3 .…”
Section: Removal Of Radioactive Iodidementioning
confidence: 99%
“…Zia et al used a Ag/Fe 3 O 4 nanocomposite which displayed an adsorption capacity of 847 mg/g for I 2 removal from aqueous media. This material exhibited high I – selectivity in the presence of competitive ions (Cl – , Br – , and PO 4 – ), good recyclability, and a removal efficiency of approximately 94% after 7 cycles . Rosenberg et al reported the removal of 131 I from soil by chemical treatment in the presence and absence of I – carrier, H 2 O 2 , and AgNO 3 .…”
Section: Removal Of Radioactive Iodidementioning
confidence: 99%
“…Liquid phase capture of iodine (as iodide or iodate) is less mature than vapor phase capture, but foundational knowledge is present. ,, The iodide or iodate can be removed through ion exchange, sorption, or precipitation as a low solubility phase (e.g., AgI, K sp = 8 × 10 –17 ). Materials demonstrated for iodine removal include MOF, Ag-based materials, , Bi-based materials, resins (for iodide), resins (for iodate), , membranes, and layered hydroxides. , However, in nearly all cases, only a single iodine species was the removal target, however, in practicality, these two species commonly coexist with one another. As both I – and IO 3 – are generated in CS, the removal of both must be considered in any such treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…However many kinds of adsorsorbent do not have sufficient advantages for iodide ion absorption. Several kinds of materials have been extensively studied as possible adsorbents, such as silver-containing material [12,13], metallic oxide [14] and metal-organic frameworks (MOFs) [15].…”
Section: Introductionmentioning
confidence: 99%